The Effectiveness of Green Marketing on Consumer Loyalty to The Body Shop Consumers in Medan City - Sagala, Natasya Agatha; Simanjorang, Feronica (PT FORMOSA CENDEKIA GLOBAL, 2024)
The environmental crisis that is getting worse and detrimental to society has encouraged the emergence of environmentally friendly marketing strategies, namely green marketing. One company that is famous for implementing green marketing in Indonesia is The Body Shop. This study aims to determine the effect of green marketing on consumer loyalty of The Body Shop in Medan City. Primary data for this study were obtained from direct interviews while secondary data were obtained through literature studies. Secondary data is obtained through literature study. This research uses a qualitative approach with an interview method with 24 related respondents conducted from April 2023 to May 2023. The results showed that green marketing has a positive effect on consumer loyalty.